Examining the Factor Structure and Measurement Invariance of the Trauma Symptom Checklist for Children in a Diverse Sample of Trauma-Exposed Adolescents. (July 2021) - Morelli, Nicholas M.; Elson, Damian; Duong, Jacqueline B.; Evans, Meghan C.; Villodas, Miguel T.
The Trauma Symptom Checklist for Children (TSCC) is a widely used youth assessment of broad, transdiagnostic symptomatology following trauma. However, its factor structure has not been thoroughly tested in diverse samples. Youth ( N = 738) exposed to interpersonal violence, including physical and sexual abuse, completed the TSCC. Confirmatory factor analysis was used to test one-, six-, and eight-factor models of the TSCC clinical scales, based on previous literature and the TSCC manual. We examined measurement invariance across boys and girls and Black and non-Black participants, as well as convergent and discriminant validity. An eight-factor structure, consisting of posttraumatic stress, anxiety, depression, anger, overt dissociation, fantasy dissociation, sexual preoccupation, and sexual distress, demonstrated the best fit, with two items removed. Invariance tests supported configural and metric (but not scalar) invariance. This research highlights the need for further testing before differences between gender and racial groups can be accurately compared.